The Impact of Urban Traffic Congestion on the Operational Costs of Logistics Transportation in Bogor City - Prasojo, Genny Luhung; Hariri, Ahmad; Abidin, Zaenal (Logistica : Journal of Logistic and Transportation, 2024)
Urban traffic congestion is a major challenge for logistics efficiency, particularly in rapidly growing cities like Bogor, Indonesia. This study aims to quantify the impact of traffic congestion on logistics operational costs by analyzing congestion levels and cost components in urban freight transport. A quantitative approach was used, involving 50 logistics fleet respondents from Bogor. Primary data were collected through structured questionnaires measuring daily congestion duration, travel time, average speed, fuel consumption, driver wages, and vehicle maintenance costs. Statistical analysis was conducted using simple linear regression. The results reveal that logistics vehicles experience approximately 95 minutes of congestion daily, with travel speeds reduced to 13.5 km/h. The study finds a strong, positive, and statistically significant relationship between congestion and logistics costs (regression coefficient = 0.674, p < 0.001), with congestion explaining 45.5% of cost variation. Increased fuel consumption, labor costs, and maintenance expenses are the main contributors to operational inefficiencies. These findings underscore how urban congestion increases the cost to serve and diminishes logistics reliability. The study suggests that policymakers adopt adaptive strategies such as smart routing, freight dedicated lanes, and urban consolidation centers. It also calls for greater integration of logistics planning in urban transport systems to enhance resilience and sustainability. These findings contribute to the growing discourse on urban freight efficiency in Southeast Asian cities.